2004
DOI: 10.1211/0022357022908
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and ocular pharmacokinetics of N-4-benzoylaminophenylsulfonylglycine (BAPSG), a novel aldose reductase inhibitor

Abstract: To better develop N- [4-(benzoylamino)phenylsulfonyl]glycine (BAPSG), a potent and selective aldose reductase inhibitor capable of delaying the progression of ocular diabetic complications, the objective of this study was to assess its pharmacokinetics. The plasma pharmacokinetics of BASPG was assessed in male Sprague-Dawley rats following intravenous, intraperitoneal and oral routes of administration and its distribution to various tissues including those of the eye was studied following intraperitoneal admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…In this study we observed that intraperitoneal administration of BAPSG after pretreatment with probenecid results in plasma BAPSG exposure (AUC 0–4hr ) of 18.2 µg-hr/ml compared to 21.7 µg-hr/ml reported previously in the absence of probenecid pretreatment (15). Thus, following intraperitoneal administration, similar BAPSG exposure was evident in the plasma with or without probenecid pretreatment.…”
Section: Resultssupporting
confidence: 49%
See 3 more Smart Citations
“…In this study we observed that intraperitoneal administration of BAPSG after pretreatment with probenecid results in plasma BAPSG exposure (AUC 0–4hr ) of 18.2 µg-hr/ml compared to 21.7 µg-hr/ml reported previously in the absence of probenecid pretreatment (15). Thus, following intraperitoneal administration, similar BAPSG exposure was evident in the plasma with or without probenecid pretreatment.…”
Section: Resultssupporting
confidence: 49%
“…In control animals, peak BAPSG levels were observed at 1 hr after dosing in all the ocular tissues except in brain (15), where BAPSG was undetectable beyond 15 min. Following pre-treatment with probenecid, retinal delivery of BAPSG at 1 hr increased by about 11-fold (2.58 vs. 0.24 µg/gm; p<0.05) (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, evidence exists for efflux transporters such as P-glycoprotein and multidrug resistance-associated proteins (MRPs) in the ocular barriers [47,7780]. Delivery of an anionic aldose reductase inhibitor to cultured human retinal pigment epithelial cells [13], as well as neural retina in vivo in a rat model [13], was elevated by probenecid treatment. This may be an outcome of drug efflux inhibition from eye tissues by probenecid.…”
Section: Key Approaches To Overcome Permeability Barriersmentioning
confidence: 99%